2005
DOI: 10.1159/000086670
|View full text |Cite
|
Sign up to set email alerts
|

FK506 (Tacrolimus) Inhibition of Intracellular Production and Enhancement of Interleukin 1α through Glucocorticoid Application to Chemically Treated Human Keratinocytes

Abstract: Purpose: Production of the proinflammatory cytokine interleukin (IL) 1α, which is stored in keratinocytes (KCs) and is multifunctional, may be enhanced by glucocorticoids. A study was made to confirm whether immunosuppressants such as the macrocyclic lactone FK506 (tacrolimus) possibly serve to modulate glucocorticoid- stimulated IL-1α production from chemically treated KCs. Methods: Usingcultured human KCs, the effects of FK506 on the production of IL-1α treated with chemicals (trinitrobenzene sulfonic acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In our study, despite long durations of treatment, telangiectasia as an adverse effect of TCPO was observed in only one patient. A possible explanation for the disparity in this observation could be the suppressive effect of TO on corticosteroid‐induced increase in interleukin‐1α production in keratinocytes, a plausible mechanism of action of TO in steroid‐induced rosacea 10 . It could be speculated that other adverse effects of topically applied corticosteroids, e.g.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In our study, despite long durations of treatment, telangiectasia as an adverse effect of TCPO was observed in only one patient. A possible explanation for the disparity in this observation could be the suppressive effect of TO on corticosteroid‐induced increase in interleukin‐1α production in keratinocytes, a plausible mechanism of action of TO in steroid‐induced rosacea 10 . It could be speculated that other adverse effects of topically applied corticosteroids, e.g.…”
Section: Resultsmentioning
confidence: 91%
“…A possible explanation for the disparity in this observation could be the suppressive effect of TO on corticosteroidinduced increase in interleukin-1a production in keratinocytes, a plausible mechanism of action of TO in steroid-induced rosacea. 10 It could be speculated that other adverse effects of topically applied corticosteroids, e.g. skin atrophy and telangiectasia, are also mitigated by combining TO with topical corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
“…In our study of K/BxN serum-induced arthritis, IL-12 p40 levels had not been different, and IL-6 and M-CSF levels tended to be altered in tg mice in comparison to WT mice (IL-1α and IL-13 levels were not determined) [8]. There is indeed evidence for a (endogenous) glucocorticoid modulation of IL-1α, IL-12 p40 and IL-13 [48-51]; however, such a modulation in osteoblasts apparently is of no relevance for AIA.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, Horiuchi et al. 35 demonstrated that tacrolimus inhibited the intracellular production and expression of IL‐1α by hydrocortisone in chemically treated human keratinocytes, suggesting the ability of topical calcineurin inhibitors to counteract the detrimental effects of glucocorticoid. Additionally, the downregulation of nitric oxide 36–38 and the growth inhibition of microorganisms such as Malassezia spp 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Pimecrolimus and tacrolimus inhibit the production and release of cytokines and proinflammatory mediators from T cells and mast cells, thereby exerting significant anti-inflammatory activity and immunomodulatory capabilities. 4 In particular, Horiuchi et al 35 demonstrated that tacrolimus inhibited the intracellular production and expression of IL-1a by hydrocortisone in chemically treated human keratinocytes, suggesting the ability of topical calcineurin inhibitors to counteract the detrimental effects of glucocorticoid. Additionally, the downregulation of nitric oxide [36][37][38] and the growth inhibition of microorganisms such as Malassezia spp.…”
Section: Discussionmentioning
confidence: 99%